Care Everywhere, a Point-to-Point HIE Tool - Winden, TJ.; Boland, LL.; Frey, NG.; Satterlee, PA.; Hokanson, JS. (Applied Clinical Informatics, 2014)
Background: Emergency departments (EDs) routinely struggle with gaps in information when providing patient care. A point to point health information exchange (HIE) model has the potential to effectively fill those gaps.Objective: To examine the utility, perceived and actual, of a point-to-point HIE tool called Care Everywhere (CE) and its impact on patient care in the ED.Methods: This mixed methods study was performed at four large hospital EDs between January 2012 and November 2012. Retrospective data was extracted from the electronic health record (EHR) to evaluate CE utilization since implementation. ED notes data were extracted from ED visits occurring between January 2012 and June 2012 and were reviewed to evaluate the impact of exchanged information on patient care.Results: Per focus group discussions, physicians thought the information received via CE was of value to patient care, particularly laboratory results, imaging, medication lists, discharge summaries and ECG interpretations. They feel the greatest impact of HIE is the avoidance of duplicative diagnostic testing and the identification of drug-seeking behavior. Nursing and ancillary staff expressed somewhat less enthusiasm but still felt HIE positively impacted patient care. Over a period of six months, CE was used in approximately 1.46% of ED encounters. A review of ED provider notes over that time period revealed CE use resulted in 560 duplicate diagnostic procedures being avoided and 28 cases of drug seeking behavior identified.Conclusion: Our study provides insight into the perceived value of HIE from the point of view of our ED physicians and staff. It also demonstrates that a point-to-point HIE tool such as Epic System’s Care Everywhere has the potential to generate greater efficiencies within the ED and impact to patient care through elimination of duplicative diagnostic imaging or testing and resource utilization associated with those procedures.Citation: Winden TJ, Boland LL, Frey NG, Satterlee PA, Hokanson JS. Care everywhere, a point-to-point HIE tool: Utilization and impact on patient care in the ED. Appl Clin Inf 2014; 5: 388–401 http://dx.doi.org/10.4338/ACI-2013-12-RA-0100
Keywords: Health information exchange; HIE; emergency department; ED